Wife for work (polygamy in the economy of the Muslim Turks of the Trans-Urals at the beginning of the 20th century) - M.I. Rodnov; L.F. Tagirova (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. The relevance of the problem is associated with the construction of the image of the past, with the formation of historical memory among local ethnic (eth-no-confessional) groups, which is one of the most controversial areas of modern humani-tarian knowledge. The purpose of the study is to analyze and summarize modern achieve-ments of historiography and compare them with new historical sources. Materials and methods. For the first time in Russian historiography, a database (big data) was created and presented to the scientific community in the amount of one and a half thousand units of measurement (household cards of the 1917 census), created on the basis of the collection of the Ufa archive (National Archives of the Republic of Bashkortostan), which was only introduced into the state archival fund of the Russian Federation in 2024 and has not been used until now, is unknown to the scientific community. In the course of processing this collection, all references to polygamy among the Turkish-speaking Muslim population of a number of volosts of Shadrinsk district of Perm province (the territory of modern Chelya-binsk region) were identified. And the information from the household cards for each peas-ant household allowed us to obtain for the first time a representative database on the econ-omy of polygamous families and conduct an analysis. Results. In the course of creating the database, a high reliability of the information potential of the household card was estab-lished. The census was conducted in the summer of 1917 on the initiative of the Provision-al Government. The left-wing parties in power openly promised the entire Russian peasant-ry a “black” redistribution of land, which encouraged respondents to answer frankly and not to hide information. Facts of concealment of information or refusal to take the census in this area are not recorded. The preservation of the household cards is good, the quality of the recording is high. The source is quite suitable for processing for a machine-readable da-tabase. The geographical scope of the sample is also representative, the database includes purely agrarian settlements and large villages located near the mining and industrial Ural industrial zone. Conclusions. To replace the narrative used in historiography in the form of fragmentary evidence and mainly from Russian (Russian-language) sources, a verified da-tabase of the Turkish-Muslim population of the Trans-Urals is introduced into scientific circulation. Statistical calculations show that polygamy was characteristic primarily of the wealthy stratum of villagers (farmers-entrepreneurs), every third of whom had two wives. Analysis of economic indicators and comparison with the demographic situation allows us to assert that the main factor in concluding a second marriage was the need for female labor.